Microwave Radiations: A Green Approach to the Synthesis of Five- Membered Heterocyclic Compounds - Kamboj, Monika; Bajpai, Sangeeta; Yadav, Monika; Singh, Surabhi (Current Green Chemistry, 2023)
Synthesis of heterocyclic scaffolds by microwave irradiation is a green and clean process. The organic transformation induced by microwave irradiation, as an alternative source of energy, has been of great interest due to the high efficiency, yield, and short reaction time with minimum by-product production. Heterocyclic compounds, an important skeleton for pharmaceuticals, are the most privileged and prevalent class of organic chemistry. They have enormous medicinal value and pharmaceutical potential. This review demonstrates the effectiveness of microwave heating for the synthesis of heterocyclic compounds. The eco-friendly microwave-induced synthesis of five-membered heterocyclic systems covering recent literature is highlighted in this article.
Keywords: Heterocyclic